Political leadership and legitimacy among the urban elite in Bangladesh - Andaleeb, Syed Saad; Irwin, Zachary T. (© 2004 Published by South Asian Studies Association of Australia, 2016)
This article was published in the Journal of South Asian Studies [© 2004 Published by South Asian Studies Association of Australia] and the definite version is available at: http://doi.org/ 10.1080/1479027042000186432 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1080/1479027042000186432